2013
DOI: 10.1007/s00259-013-2345-7
|View full text |Cite
|
Sign up to set email alerts
|

Tumour volume delineation in prostate cancer assessed by [11C]choline PET/CT: validation with surgical specimens

Abstract: The choline uptake pattern corresponded to the histological localization of prostate cancer in fewer than 50 % of lesions. Even when corresponding visual choline uptake was found, this uptake was highly variable between patients. Therefore SUV thresholding with standard algorithms did not lead to satisfying results with respect to defining tumour tissue in the prostate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(24 citation statements)
references
References 33 publications
0
21
1
1
Order By: Relevance
“…Only 46% of histopathologically positive lesions had increased 11 C-choline uptake. The authors could not determine a specific SUV threshold for distinguishing tumor tissue from nontumor tissue (20). Those results were confirmed by Grosu et al, who showed that correct differentiation of malignant from normal prostate tissue with 11 C-choline PET/CT was not feasible (21).…”
Section: Diagnosis Of Pcmentioning
confidence: 89%
See 2 more Smart Citations
“…Only 46% of histopathologically positive lesions had increased 11 C-choline uptake. The authors could not determine a specific SUV threshold for distinguishing tumor tissue from nontumor tissue (20). Those results were confirmed by Grosu et al, who showed that correct differentiation of malignant from normal prostate tissue with 11 C-choline PET/CT was not feasible (21).…”
Section: Diagnosis Of Pcmentioning
confidence: 89%
“…There was no significant difference between the SUV max of malignant changes and the SUV max of benign prostatic changes (18). Bundschuh et al correlated 11 C-choline uptake in the prostate gland with histopathologic findings after radical prostatectomy (20). Only 46% of histopathologically positive lesions had increased 11 C-choline uptake.…”
Section: Diagnosis Of Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Others have reported that choline uptake corresponded to histological localisation of the tumour in fewer than 50 per cent of cases, with a great deal of interpatient variability. 9 Some have not even been able to demonstrate significant difference in 18 F-choline uptake between benign and malignant prostate lesions. 10 Currently there is not enough evidence to recommend the use of choline-PET/CT as a first-line screening procedure.…”
Section: Role Of Choline-pet/ct In Prostate Cancer Diagnosismentioning
confidence: 99%
“…For the PET component, only focal uptake greater than background prostate uptake was classified as being PET positive. Reports were correlated with whole-mount histopathology results, with volume correction for tissue shrinkage (in vivo volume = ex vivo fixed volume x 1.3) [275]. Statistical analyses such as sensitivity, specificity, positive predictive value (PPV) and negative predictive value (NPV) were calculated with SPSS Statistics (IBM Corp.…”
Section: Mp Mri Component Of Hybrid Pet/mrimentioning
confidence: 99%